Spirits of the Air: Birds and American Indians in the South - E. N. Anderson (Ethnobiology Letters, 2010)
Review of Spirits of the Air: Birds and American Indians in the South. Shepard Krech III. 2009. University of Georgia Press, Athens. Pp. 245, copiously illustrated. $44.95 (hardbound). ISBN-13 978-0-8203-2815-7.